Scaling Up TiO2 Anodization Device For Gas Phase Photocatalysis - Muhammad Azrul Iqbal, Mohd Azri (2022)
Carbon dioxide (CO2) emissions are defined as releasing greenhouse gases and their precursors into the atmosphere over a defined area and period that harm living things at the surface. One of the best ways to solve the CO2 problem is to use solar energy to photocatalytically convert CO2 to hydrocarbons, generating renewable energy and photocatalytic CO2 reduction using either artificial light or sunlight and demonstrating the fundamental mechanism of CO2 photoreduction. Photocatalytic reactions on TiO2 have lately seen a massive rebirth due to several novel tactics and discoveries that promise to dramatically boost the efficiency and specificity of such reactions by changing the titania scaffold and chemistry. Anodization, sol-gel, hydrothermal method, sonoelectrochemical, microwave irradiation, and alkaline synthesis are among the methods available for the production of TiO2 Nanotubes. Among these methods, anodization is chosen. This research aims to design and fabricate the anodization reactor for TiO2 nanotubes layers for gas-phase photocatalysis. Electrochemical anodization is the most widely used method because of its controllable, repeatable results in a single process, the ability to tune the size and shape of nanotubular arrays to the desired dimensions, and the ability to meet the demands of specific applications through controlled anodic oxidation of the metal substrate. It is also a cost-effective method, and the tubes created this way have good adherent strength. Furthermore, anodization parameters can easily control the thickness and morphology of TiO2 films. The electrochemical anodization method was used as the anodization process to make the TiO2 nanotubes. The material and the design were carefully chosen to make the anodization perfect. The amount of TiO2 that can be produced can be increased by scaling up the anodization process. Several tests will be run to prove that the scaling up using the anodization was a success. The test used was Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-Ray Spectroscopy (EDX) and Cryogenic Transmission Electron Microscopy (Cryo-TEM). The use of CO2 as a fuel in ovens, houses, and trucks highlights the benefits of converting to CH4, which may even be used to generate energy. The consequent slew of global environmental issues poses a significant threat to human survival and the planet. As a result, it is a substantial obstacle to humanity's ability to lessen its reliance on fossil fuels and convert CO2 into added-value chemicals and fuels